Measuring the impact of trade shocks on poverty in Iraq using the self-regression model for 2007-2014 - Zaher, Abdalhamed S.; Ahmed, Deldar H. (Humanities Journal of University of Zakho, 2017)
This study aims to determine the direction of the causal relationship between trade shocks and poverty using quarterly data for 2007-2014. To achieve the objectives of the study Vector Error Correctio Model (VECM) was used, which is one of the form of Vector Autoregression Models (VAR), that is because there is a mutual cointegration and a long-term equilibrium relationship between the model variable, also, (Granger Casuality) test, (Variance decomposition) test and (Impulse response) test were applied. The study results have shown that there is a one-way causal relationship of the GDP, oil price and oil rent rate of Gross domestic product to poverty ratio, while the relationship between government spending and poverty ratio was bidirectional, The study concluded that there could be reduction in poverty ratio through economic policies that work to developing and diversifying productive base to assure job opportunities for more people and thus reducing unemployment and poverty.